Teachers of English and their Perceptions towards ESL Errors - Maharjan, Laxmi Bahadur (Mangal Research Journal, 2022)
This study entitled 'Teachers of English and their Perceptions towards ESL Errors' aimed at evaluating and determining gravity of grammatical errors in terms of acceptability and intelligibility judgments. Quantitative research methodology was utilized in this study. The data was gathered with the aid of a questionnaire prepared on the basis of the result of error analysis conducted earlier. The questionnaires were mailed to English teachers of different private and public schools, colleges and universities of Nepal and worldwide. Two hundred twenty (220) useable surveys were collected altogether for the study: 100 surveys from Nepali English teachers, 100 surveys from native English speaking teachers, 20 each from Britain, Australia, New Zealand, Canada and America, and likewise, 20 surveys from non-Nepali English teachers. Received responses were analyzed and explained descriptively. The findings of the study showed that the native English teachers evaluated the errors far more leniently than Nepali and non- Nepali English teachers. There is no any significant difference in evaluation of errors found in between Nepali and non-Nepali English teachers, but compared to native English teachers, they were found statistically and significantly different in their judgments of errors in acceptability and intelligibility both. On the other hand, while comparing judgments of learners' errors in between the native English teachers; it was revealed that there were not any significant differences found there. It is recommended that the native English speaking teachers’ perception of errors be rightly explored and accordingly evaluation scales be developed and the teachers be made aware of such universal rating scales of grammatical errors while evaluating learners' errors.